Pengaruh luas lahan pertanian dan nilai realisasi proyek penanaman modal asing terhadap emisi gas rumah kaca di Kabupaten Batang Jawa Tengah - Audia, Desinta; Raras Saputri, Nimas Alfiana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The continuous increase in greenhouse gas emissions has a negative impact on climate change. This study aims to determine the effect of agricultural land area and the realized value of foreign investment projects on greenhouse gas emissions as a result of the development of the Batang Integrated Industrial Estate (KITB). Industrial development and economic development are interrelated things. The many positive impacts caused by industrial development are not always realized because of the negative impacts. One of them is the emission of greenhouse gases. This is a quantitative study that employs multiple linear regression analysis with random effects. The results showed that the decrease in agricultural land by 36.8x and the increase in project realization value by 12x had an effect on increasing greenhouse gas emissions. The development of KITB has a positive impact on economic growth and reduces unemployment. However, attention to environmental management should also be implemented from the start of construction, so that the level of air pollution can always be controlled.